Avaliação da arborização de acompanhamento viário da cidade de São Tomé, Paraná - Silva, Otávio Henrique da (2013)
The quality of life has been increasingly a concern of the modern man and it fits in this perspective the concept of urban forestry, mainly due to the benefits it provides, such as environmental comfort, psychological well-being and psychological assistance to people and improvement of aesthetic effect. This study aimed to evaluate the afforestation along the avenues in São Tomé, Paraná. In order to do this a census was carried out of all samples taller than 1 (one) meter present along the thoroughfares of the city, and further analysis of the found species regarding the fulfillment of the technical standards on qualitative aspects: origin, existence of large freshy fruits and toxic principle and the presence of thorns and aculei, respectively, and then the quantification and classification of the damage of roots and crowns to public equipment. 71 different vegetal species were verified, with a total of 3107 individuals, predominantly with Licania tomentosa (Benth.) Fritsch (Chrysobalanaceae) (n = 1120) and Poincianella pluviosa var. peltophoroides (DC.) LP Queiroz (Fabaceae- Caesalpinioideae) (n = 646). After analysing of the indicated parameters, has been suggest the replacement of 646 samples of 47 species (20,79% of total incidence) per vegetal species suitable to the technical standards. Among the 24 suitable species for use in the thoroughfare afforestation found in the city, stand out Handroanthus chrysotrichus (Mart. ex DC.) Mattos (Bignoniaceae), Handroanthus heptaphyllus Mattos (Bignoniaceae) and Tabebuia roseoalba (Ridl.) Sandwith (Bignoniaceae), due to the benefits they bring to the population, as well as their characteristics which are compatible with the people’s safety. Keywords: